Paint -- pigments, drying oils, polymers, resins, naval stores, cellulosic esters, and ink vehicles - International, ASTM. ([S.l.] : ASTM International, 2009)
Includes specifications and test methods that establish property requirements for various pigments, including white, black, bronze, blue, and red; drying oils; resins; and polymers.